A Survey of IPEG-Middle East Chapter members to ascertain their perceptions of, and changes to, the Nissen's wrap design and the outcomes - Hamed M. Seleim; Basma Magdy; Amel Hashish (Annals of Pediatric Surgery, 2023)
Abstract Background Nissen's description of fundoplication has proven seminal in our understanding of anti-GERD surgeries. This survey aimed to ascertain the perceptions of, and changes to, the Nissen's wrap design among the IPEG-ME surgeons and their outcomes. Methods During the months of February and March 2021, all IPEG-ME members were contacted via WhatsApp and asked to complete an anonymous online survey. Google Forms was used as the platform for the survey. Responses were collected over a four-week period. Results From a total of 99 IPEG-ME members, 51 practicing pediatric surgeons from eight countries reported seven separate conceptions for the original Nissen wrap design. With more surgeon years of experience, not hospital annual volume, the percentage of surgeons who choose to preserve the short gastric vessels at laparoscopic Nissen fundoplication increased from 10 to 25%. Moreover, transmigration and reoperation rates were cut in half, while dysphagia rates doubled as surgeon years of experience increased from under 10 to over 30. Conclusion Owing to haziness, specialized surgeons may have expressed non-identical thoughts of the original description of a commonly employed procedure. Wrap transmigration and reoperation rates were cut in half, while dysphagia rates doubled as surgeon years of experience increased from under 10 to over 30. It seems reasonable to standardize the wrap design based on the components' justifications rather than surgeons’ preferences.